Association of Irritable Bowel Syndrome with Somatization - Ali Hyder Mugheri, Shabana Lakho, Amjad Hussain Balouch, Fozia Unar, Hina Naz Bozdar, Khushbo Jawed Samo (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the association of irritable bowel syndrome with somatization. Study Design: Prospective study Prospective study Place and Duration of Study: Department of Gastroenterology, Chandka Medical College @ Shaheed Mohtarma Benazir Bhutto Medical University, Larkana from 1st May 2021 to 31st October 2021. Methodology: Fifty patients suffering from somatization were registered from the hospital based setting. Symptoms checklist 90 revised as SCL-90 revised psychopathological symptoms measuring tool was applied for measuring somatization. Gastrointestinal Symptoms-Rating Scale (GSRS) was also applied which used seven level Likert scale based on frequency, intensity of GI symptoms within last 7 days. Demographic information, clinical co morbidity associations, family history was also recorded. Results: Irritable bowel syndrome presented in only 14% males while it was seen in 34% females. High scored somatization was more common in females. The statistical analysis showed that there was a significant difference in the severe abdominal pain between low and high somatization cases with IBS. A high scoring of indigestion and diarrhea was also noticed in the high somatization cases of IBS. High level of somatization (58% cases) was observed within the irritable bowel syndrome cases. Conclusion: Somatization exacerbates the symptom profile of irritable bowel syndrome patients that need to be timely and properly assessed.